Functional identification of Arabidopsis stress regulatory genes using the Controlled cDNA Overexpression System - Ábrahám, Edit (Acta Biologica Szegediensis, 2008)
Plants respond to environmental stresses by altering the expression of many genes via a complex signalling network. We created a Controlled cDNA Overexpression System (COS) to identify genes and regulatory factors which have important role in stress tolerance. An estradiol-inducible cDNA expression library was tested in three genetic screens by selecting for salt tolerance, ABA insensitive germination and activation of a stress responsive ADH1-LUC reporter gene construct. Several cDNAs conferring dominant, estradiol dependent stress tolerance phenotypes were identified. Screening for enhanced salt tolerance revealed that estradiol-controlled overexpression of 2-alkenal reductase (AER) cDNA confers considerably high level of salt insensitivity. Characterization of cDNA conferring insensitivity to 3μM ABA in germination assays has identified the full-length coding region of heat shock protein HSP17.6A, suggesting its implication in ABA signal transduction. Screening for transcriptional activation of ADH1-LUC reporter gene has identified the ERF/AP-type transcription factor RAP2.12, which sustained high level ADH1-LUC bioluminescence and enhanced ADH1 transcription in the presence of estradiol. Our data illustrate that application of inducible cDNA expression libraries such as the COS system provides an efficient tool for genetic identification and functional analysis of novel regulators of abiotic stress responses.